Correlational anatomy of biceps brachii muscle with its footprint and aponeurosis parameters - Suresh Narayanan (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: The anatomy of the distal biceps tendon (DBT) and its insertional anatomy to radial tuberosity is important to understand the pathophysiology of tendon rupture and in surgical repair of the ruptured tendon. The present study aimed to evaluate the relationship between biceps brachii parameters with biceps footprint and lacertus fibrosus (LF) parameters. Materials and Methods: This was a cross-sectional observational study done on 23 cadavers. The biceps brachii perimeters, the length of the DBT, distance between the radial head and radial tuberosity, footprint length, footprint breadth, and LF width were noted (with measuring tape and digital vernier caliper. LF angle was measured using Image J software. Results: There was a weak positive correlation between biceps brachii perimeter and footprint length (r = 0.392), biceps brachii perimeter and footprint breadth (r = 0.341), biceps brachii perimeter and LF width (r = 0.300), and moderate positive correlation between footprint length and breadth (r = 0.686). Conclusion: The biceps brachii perimeter has a minimal role in influencing the footprint dimensions and LF morphology. The study has explored the biomechanical aspect of the biceps brachii insertional anatomy. The data on footprint dimension and aponeurosis could help the surgeons in the effective repair of the ruptured tendon and achieving a better postoperative outcome.